REDOX AND SPECIATION OF TIN IN HYDROUS SILICATE GLASSES: A COMPARISON WITH NB, TA, MO AND W - Farges F.; Brown G.E.; Linnen R.L. (My University, 2006)
The speciation of tin in nine hydrous haplogranitic silicate glasses (0.1-1 wt.% SnO2) was investigated by XAFS spectroscopy at the tin K-edge. Three compositions of granitic melt were investigated [peralkaline (ASI 0.6), metaluminous (ASI 1.0), and peraluminous (ASI 1.2)] and, for each of these, tin-bearing glasses were synthesized at three different redox conditions (~FMQ, ~FMQ + 1.1, and ~FMQ + 2.4). The hydrous glasses were quenched from H2O-saturated melts at 850°C and 2 kbar. Redox states estimated from XANES are in good agreement with those estimated from SnO2 dissolution experiments. There are, however, some unresolved discrepancies. Tetravalent Sn is dominant in all peralkaline melts investigated, even at FMQ. In contrast, Sn(II) is dominant in the peraluminous compositions investigated, even at FMQ + 2.4. The tin K-edge XAFS spectra for the oxidized glasses resemble that of eakerite [Ca2 SnAl2 Si6O18 (OH)2•2H2O]. Tetravalent Sn thus behaves in a similar manner to Zr(IV), a network modifier, but is markedly different from Ti(IV), a network former. In the most reduced glasses, highly ionic Sn(II)-bearing moieties are formed. Thus, Sn(II) is comparable to Ca2+, i.e., it is an efficient network modifier, in sharp contrast to Sn(IV), Consequently, Sn(IV) is soluble in silicate melts that contain non-bridging oxygen (NBO) atoms, such as peralkaline compositions. In contrast, in peraluminous magmas, in which NBO are lacking, Sn(II) preferentially forms highly ionic moieties that can be easily "complexed" and transported by, for instance, chlorine. If the redox conditions become oxidizing, Sn(IV) forms, but cannot accommodate itself within the framework of tetrahedra of the melt structure, which results in nucleation of cassiterite. In a comparison of speciation information for Nb(V), Ta(V), W(VI) and Mo(VI) in similar compositions of glass, Sn(IV) acts more like Nb(V), Ta(V) or Zr(IV), whereas Mo(VI) and W(VI) form highly covalent complexes (sensu stricto) that are disconnected from the framework of tetrahedra. Tin geochemistry in melts appears to be dominated by an exchange between two highly different structural positions for Sn(IV) and Sn(II), which is highly sensitive to peralkalinity under conditions of moderate fugacity of oxygen. In contrast, the mineralogy of tin is dominated by Sn(IV). The difference in the valence of tin in melts vs minerals makes it a very unusual cation as compared to other highly charged cations to which tin is commonly associated, such as Mo, W, Ta and Nb.
Keywords: HIGHLY CHARGED CATIONS; HYDROUS GLASSES; SOLUBILITY; TIN; XAFS SPECTROSCOPY